Is perception of VAR outcome biomechanically accurate? - Soltani, P. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this study was to understand if offside judgments, using different video assistant referee (VAR) technologies (video replay vs. guiding lines), are biomechanically accurate. Ten college students viewed video clips of a football player, receiving the ball from his teammate, and from different camera angles. Participants were asked to determine the ball-kick moment and to judge whether the ball receiver was in offside. Participants` responses were verified with the kinematic parameters of the ball and the players. Participants` judgements were on average 132 ms later than the actual offside moment. While camera angles did not affect their judgements, participants had higher correct judgments at 0 and 90° viewing angles and when VAR guiding lines were present.